2011
DOI: 10.1002/cne.22762
|View full text |Cite
|
Sign up to set email alerts
|

Subdivisions of the turtle Pseudemys scripta hypothalamus based on the expression of regulatory genes and neuronal markers

Abstract: The patterns of distribution of a set of conserved brain developmental regulatory transcription factors and neuronal markers were analyzed in the hypothalamus of the juvenile turtle, Pseudemys scripta. Combined immunohistochemical techniques were used for the identification of the main boundaries and subdivisions in the optic, paraventricular, tuberal, and mammillary hypothalamic regions. The combination of Tbr1 and Pax6 with Nkx2.1 allowed identification of the boundary between the telencephalic preoptic area… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
99
0

Year Published

2013
2013
2015
2015

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 56 publications
(119 citation statements)
references
References 128 publications
(226 reference statements)
20
99
0
Order By: Relevance
“…4a in Moreno et al, 2012a]. Consistent with this proposal, in the present study, we found that the chicken Ceov is populated by cells derived from the Stv, and some of these cells were found to express Islet1 ( fig.…”
Section: The Chicken Ceov Is Populated By Stv-derived Neurons Expresssupporting
confidence: 79%
See 4 more Smart Citations
“…4a in Moreno et al, 2012a]. Consistent with this proposal, in the present study, we found that the chicken Ceov is populated by cells derived from the Stv, and some of these cells were found to express Islet1 ( fig.…”
Section: The Chicken Ceov Is Populated By Stv-derived Neurons Expresssupporting
confidence: 79%
“…A similar group has also been identified in reptiles [Martínez-García et al, 2007Moreno et al, 2012a]. Based on their relation to distinct embryonic Pa subdomains, we proposed the existence of dorsal and ventral subdivisions of the chicken BSTL, with the BSTLd being related to the Pad and being part of the EAce, and the ventral BSTL being related to the Pavc and, as such, being part of the medial extended amygdala or EAme [Abellán and Medina, 2009].…”
Section: The Chicken Dorsal Bstl Includes Pallidal and Striatal Cellsmentioning
confidence: 96%
See 3 more Smart Citations